PENGEMBANGAN VIDEO PEMBELAJARAN BUDAYA 5S (SENYUM, SALAM, SAPA, SOPAN, DAN SANTUN) UNTUK PENGURUS OSIS SMAN 5 ENREKANG - Syahrul Gunawan; Citra Rosalyn Anwar; Merrisa Monoarfa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study developed a 5S Culture learning video on OSIS SMAN 5 Enrekang. The purpose of this study was to 1) determine the level of need for learning video media, 2) design learning video media, 3) determine the validation of learning video media, 4) determine the practicality of learning video media. The approach used in this study is development (R&D) with the development model used, namely ADDIE (analysis, design, development, implementation, evaluation). The data sources in this study were 30 students, 1 instructor, and 2 validators consisting of material/content validators and media validators. Data collection techniques were in the form of questionnaires. Data analysis techniques used qualitative descriptive analysis and quantitative descriptive analysis in the form of needs identification questionnaires, material/content validation questionnaires, media validation questionnaires, small group trial questionnaires, large group/field trial questionnaires, OSIS SMAN 5 Enrekang instructor assumption questionnaires. The results of the study showed that the results obtained from the identification of the level of student needs were in the qualification of being quite needed. 2) The results obtained from the validation of material/content experts were in the qualification of being very valid and the validation of media experts were in the qualification of being very valid. 4) To test the level of practicality of the product, small group trials, large group trials and supervisor responses were conducted. From the three trials, the results obtained were very good qualifications.